Fractography of Stress Corrosion Cracking of 20% Cold Worked Type 304 H Stainless Steel Containing δ-Ferrite in Oxidizing Primary Water - Kim, Hong-Pyo; Lee, Jong-Yeon; Cho, Sung-Hwan; Choi, Min-Jae; Kim, Sung-Woo; Jin, Hyung-Ha; Kim, Dong-Jin; Hwang, Seoung-Sik; Lim, Yun-Soo (Archives of metallurgy and materials, 2024)
Fractography of stress corrosion cracking (SCC) of 20% cold worked Type 304 H stainless steel containing δ-ferrite was studied using a compact tension (CT) specimen in oxidizing primary water with a scanning electron microscope (SEM) and electron back scattered diffraction (EBSD). The stress corrosion crack propagated mostly in transgranular stress corrosion cracking (TGSCC) mode and sometimes in intergranular stress corrosion cracking (IGSCC) mode. TGSCC paths were along the {111} plane with both high resolved shear stress and high resolved tensile stress. IGSCC preferentially propagated along the grain boundary perpendicular to the loading axis. The findings in this work suggest that TGSCC proceeds through formation of a weakening zone at the head of the crack tip by interaction of slip and corrosion and then cracking of the weakened zone by tensile stress.